Analysis Of Students' Problem-Solving Abilities Based on Cognitive Style - Purnamasari, Ika (Prima: Jurnal Pendidikan Matematika, 2024)
This research departs from the problem that students do not have adequate mathematical ability to solve complex problems. This study aims to investigate students' mathematical problem-solving skills based on cognitive styles and identify the difficulties students face in solving problems. The research method used was an explanatory sequential mixture conducted at SDN Ncera, and the research subjects were selected using purposive sampling. The test instruments used are MFFT, description test, and interview. Data analysis uses quantitative descriptive analysis and qualitative descriptive analysis. The results showed that 1) grade V students of SDN Ncera with impulsive cognitive styles were more than students with reflective cognitive styles in mathematical problem-solving skills. Impulsive students tend to be rushed and less check their answers, resulting in incorrect solutions, while reflective students provide more accurate solutions even if it takes longer. 2) The results of the identification of students' difficulties in solving problems showed that students with a reflective cognitive style already understood information formulas and could solve problems related to the area of the parallelogram. However, he did not re-examine his work and conclude the results of his work. Meanwhile, students with impulsive cognitive styles showed that students experienced difficulties, especially in the steps of implementing the plan and checking the final results. Students make mistakes in calculations because they do not spend enough time and are not thorough.